Chapter Massimo Quaini e il CISGE - Rossi, Massimo (Territori, 2021)
Among the geographical associations the Italian Centre for Historical and Geographical Studies (CISGE) was the one with which Massimo Quaini maintained a stronger relationship. In addition to the sharing of the study fields, Quaini was also linked to CISGE by the close and inseparable link between geography and history, the combination of concrete research and theoretical reflection, the plurality of approaches, the continuous dialectic and the marked interdisciplinarity. Elements that have always characterized the Centre since its foundation, becoming concrete in meetings, seminars, conferences, research groups, national and international projects and in numerous publications. Through a careful analysis of Quaini's writings contained in the proceedings, the collections of essays and the journal Geostorie (which since 2000 replaced the Notiziario del CISGE) - a long and uninterrupted series from 1992 to 2017 - the contribution aims at highlighting the original, critical and stimulating contribution offered by Massimo to the four fundamental study streams of CISGE: historical geography, history of cartography, history of geographical thought, history of travels and of explorations.